A method for selective and efficient isolation of gray matter astrocytes from the spinal cord of adult mice - Ryoma Iwasaki; Yuta Kohro; Makoto Tsuda (Molecular Brain, 2024)
Abstract A growing body of evidence indicates intra- and inter-regional heterogeneity of astrocytes in the brain. However, because of a lack of an efficient method for isolating astrocytes from the spinal cord, little is known about how much spinal cord astrocytes are heterogeneous in adult mice. In this study, we developed a new method for isolating spinal astrocytes from adult mice using a cold-active protease from Bacillus licheniformis with an astrocyte cell surface antigen-2 (ACSA-2) antibody. Using fluorescence-activated cell sorting, isolated spinal ACSA-2+ cells were divided into two distinct populations, ACSA-2high and ACSA-2low. By analyzing the expression of cell-type marker genes, the ACSA-2high and ACSA-2low populations were identified as astrocytes and ependymal cells, respectively. Furthermore, ACSA-2high cells had mRNAs encoding genes that were abundantly expressed in the gray matter (GM) but not white matter astrocytes. By optimizing enzymatic isolation procedures, the yield of GM astrocytes also increased. Therefore, our newly established method enabled the selective and efficient isolation of GM astrocytes from the spinal cord of adult mice and may be useful for bulk- or single-cell RNA-sequencing under physiological and pathological conditions.